Long-term care units: a Portuguese study about the functional profile - Fonseca, César; Ramos, Ana; Morgado, Bruno; Quaresma, Paulo; Garcia-Alonso, José; Coelho, Anabela; Lopes, Manuel (Frontiers in Aging, 2023)
Aim: In this study, we analyze the relationship between the functional profile of older people admitted to long-term care units in Portugal and some demographic variables such as education level, sex, and age as well as the emotional state of mind. Methods: A sample of 59,516 older people from the National Network of Integrated Continuous Care of Portugal were analyzed in this longitudinal study. All the retrospective data of the older people were collected during the period of hospitalization at the long-term care units. The database records of these units were analyzed, and a functional profile spanning the period of hospitalization was calculated. Results: Activities of daily living and cognitive states improved, in the first 90 days of hospitalization, while mobility and instrumental activities of daily living worsened for the same period of 90 days. Generally, there was a decline in all domains after 450 days of hospitalization. The older women that didn’t attend school, those over 85 years old, and those who suffered from anxiety were pre-dominantly placed in the group of those with greater dependence (severe/complete dependence). Conclusions: The participants hospitalized between 90 and 360 days presented the best results in the long-term care units of the National Network of Integrated Continuous Care of Portugal. With this study, we highlight the importance of evaluating the functional status of persons in long-term hospitalizations and the influence exerted by the level of education on the recovery and rehabilitation of dependence.